NK Cell-Dependent Antibody-Mediated Immunotherapy Is Improved In Vitro and In Vivo When Combined with Agonists for Toll-like Receptor 2 in Head and Neck Cancer Models - Gruijs, Mandy; Ganzevles, Sonja H.; Stigter-van Walsum, Marijke; van der Mast, Richard; van Ostaijen-ten Dam, Monique M.; Tuk, Cornelis W.; Schilham, Marco W.; Leemans, C. René; Brakenhoff, Ruud H.; van Egmond, Marjolein; van de Ven, Rieneke; Bakema, Jantine E. (International journal of molecular sciences, 2021)
The immunosuppressive character of head and neck cancers may explain the relatively low response rates to antibody therapy targeting a tumor antigen, such as cetuximab, and anti-PD-1 checkpoint inhibition. Immunostimulatory agents that overcome tumor-derived inhibitory signals could augment therapeutic efficacy, thereby enhancing tumor elimination and improving patient survival. Here, we demonstrate that cetuximab treatment combined with immunostimulatory agonists for Toll-like receptor (TLR) 2 induces profound immune responses. Natural killer (NK) cells, isolated from healthy individuals or patients with head and neck cancer, harbored enhanced cytotoxic capacity and increased tumor-killing potential in vitro. Additionally, combination treatment increased the release of several pro-inflammatory cytokines and chemokines by NK cells. Tumor-bearing mice that received cetuximab and the TLR2 ligand Pam3CSK4 showed increased infiltration of immune cells into the tumors compared to mice that received cetuximab monotherapy, resulting in a significant delay in tumor growth or even complete tumor regression. Moreover, combination treatment resulted in improved overall survival in vivo. In conclusion, combining tumor-targeting antibody-based immunotherapy with TLR stimulation represents a promising treatment strategy to improve the clinical outcomes of cancer patients. This treatment could well be applied together with other therapeutic strategies such as anti-PD-(L)1 checkpoint inhibition to further overcome immunosuppression.